Evaluasi Distribusi Benih Pisang dalam Program "Nagari Mandiri Pangan" di Kabupaten Padang Pariaman, Sumatera Barat - Dian Hafizah; Faidil Tanjung; Rusda Khairati; Rini Hakimi; Ilham Akbar (Journal of Integrated Agribusiness, 2024)
The purpose of this study is to evaluate the distribution of bananas in the Nagari Mandiri Pangan Program in Padang Pariaman Regency, West Sumatra. Nagari Mandiri Pangan is a program implemented by the West Sumatra government. This program is an adaptation of the Desa Mandiri Pangan launched by the Food Security Agency of the Ministry of Agriculture (BKP) at the national level. The West Sumatra Government is trying to explore the needs of the farmers themselves. In this case, farmers who are in the group ask to be given banana seed assistance, which is a commodity that has the potential to be developed. This research was carried out on five farmer groups in Padang Pariaman Regency. The method used is an interview using a questionnaire, which is then analyzed using descriptive statistics. The existing results are compared with the technical guidelines and implementation guidelines that have been prepared. From the results, it was found that the distribution of banana seeds was carried out during the current year, and the requests from farmer groups could be accommodated through this program. Banana plants were chosen because this commodity has suitable growing conditions at the research site. Farmers are obliged to provide land that is used from existing vacant land and land that was previously unused. In addition, farmers are obliged to maintain bananas that have been given properly and provide periodic reporting. To ensure that farmers carry out their obligations, the agency evaluates by visiting and providing assistance with good banana cultivation methods in collaboration with local extension workers.